Le Terme Centrali di Porto Torres (SS): rilievo e ricostruzione 3D (ACME, 2023)
The paper aims to present the methods and results of the virtual restoration project of a sector of the ancient Porto Torres/Turris Libisonis (central baths, adjacent street and facing shops - the so-called Palazzo del Re Barbaro); the project is the result of a collaboration agreement between the Regional Museums Direction of Sardinia and the University of Padua. The method applied is based on Virtual Reality fruition technologies and has enabled virtual restoration as well as the geolocalising the 3D virtual model on-site: an App commands the display of equirectangular images inside VR viewers, allowing ‘augmented’ guided tours. The work started with an annotated bibliographic collection, which was followed by a photogrammetric survey campaign by drone (carried out by G. Alvito, Teravista); finally, interweaving the collected data, the virtual 3D reconstruction of the buildings was carried out. The structural evidence preserved today was integrated into the 3D scene with coeval comparisons (3rd century AD), virtually reconstructed and relocated in plausible contexts of use, thus increasing reconstructive reliability. The entire reconstruction process was bound to a rigorous scientific validation process based on the Extended matrix method, and the final outcome is now usable both through traditional projections (off-site, presented at tourismA 2020 exhibition) and through the use of mobile VR devices (on-site, presented at the European Heritage Days 2020). On these and other occasions, there has been an excellent response from the public, facilitated by the virtual in their perception and understanding of the ancient architectural evidence.